2018
DOI: 10.3233/adr-170042
|View full text |Cite
|
Sign up to set email alerts
|

Increased All-Cause Mortality by Antipsychotic Drugs: Updated Review and Meta-Analysis in Dementia and General Mental Health Care

Abstract: It is almost ten years since the Banerjee 2009 report established that inappropriate prescribing of antipsychotics in the elderly was occurring in the UK and such patients had an 85% increased risk of adverse events and greater mortality. This report was a critical analysis addressing the outcomes of treatment practices for dementia in UK patients and globally, aimed at reducing prescribing of antipsychotic drugs for dementia. Since 2009, many significant studies worldwide (including several more recent large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 92 publications
7
114
0
3
Order By: Relevance
“…This was also true for Māori with dementia (HR:3.62, 95% CI: 0.79, 16.7) although did not reach statistical significance, probably due to smaller sample size and therefore reduced number of death events (n = 7). It is well established that antipsychotics increase the risk of mortality in people with dementia . The reason that this risk might be increased in Pacific Islanders and Māori may be due to their pre‐existing increased risk of stroke and cardiovascular events; however, these factors should be controlled for in our analysis as the final model included adjustment for comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also true for Māori with dementia (HR:3.62, 95% CI: 0.79, 16.7) although did not reach statistical significance, probably due to smaller sample size and therefore reduced number of death events (n = 7). It is well established that antipsychotics increase the risk of mortality in people with dementia . The reason that this risk might be increased in Pacific Islanders and Māori may be due to their pre‐existing increased risk of stroke and cardiovascular events; however, these factors should be controlled for in our analysis as the final model included adjustment for comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that antipsychotics increase the risk of mortality in people with dementia. 30 The reason that this risk might be increased in Pacific…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…A type of medication called antipsychotics may be prescribed to treat hallucinations, aggression and agitation. However, research has shown that some antipsychotics are associated with an increased risk of stroke and death in individuals with dementia 47,48 . The decision to use antipsychotics must be considered with extreme caution.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…However, research has shown that some antipsychotics are associated with an increased risk of stroke and death in individuals with dementia. 47,48 The decision to use antipsychotics must be considered with extreme caution. The FDA has ordered manufacturers to label such drugs with a "black box warning" about their risks and a reminder that they are not approved to treat dementia symptoms.…”
Section: Signs Of Alzheimer's or Other Dementias Typical Age-relatedmentioning
confidence: 99%
“…Although the reasons are not well defined, antipsychotic medications are also associated with increased mortality in vulnerable populations receiving off-label prescriptions including children [12] and older adults [13][14]. Clinical data indicate that schizophrenic patients are more susceptible to infections [15]; the role of medications, per se, on the increased susceptibility to infections in this population has not been clearly delineated.…”
Section: Introductionmentioning
confidence: 99%